Changes in Polyphenols Contents and Antioxidant Capacities of Organically and Conventionally Cultivated Tomato (Solanum lycopersicum L.) Fruits during Ripening - Dea Anton; Ingrid Bender; Tanel Kaart; Mati Roasto; Marina Heinonen; Anne Luik; Tõnu Püssa (International Journal of Analytical Chemistry)
Polyphenols of fruits and vegetables form an important part of human dietary compounds. Relatively little is known about accumulation of phenolics during fruits ripening process. The goal of this work was to study the changes in antioxidant activity and in content of 30 polyphenols during ripening of tomato fruits. Five organically and conventionally grown tomato cultivars were investigated at three different ripening stages. Phenolic compounds were extracted with methanol and extracts were analyzed by HPLC-DAD-MS/MS. During ripening, four different changing patterns were observed: (1) high level in green fruits with minimal changes; (2) continuous increase with maximum level in red-ripe fruits; (3) decrease; (4) increase and achieving maximum level at half-ripe stage. Similar change patterns were found for organic and conventional fruits. The accumulation patterns of phenolic compounds were similar in standard-type tomatoes but differed in several cases in cherry-type cultivar. Although contents of some polyphenols decreased during ripening, total phenolics and free radical scavenging activity increased in all studied cultivars and in case of both cultivation modes. The changes in content of phenolic compounds during ripening were greatly influenced by cultivars, but cultivation mode had only minor impact on dynamics in polyphenols contents in tomato fruits.